Structures in the Hanging wall of the Main Boundary Thrust, Post- Folding Thrust and Normal Faults from the Kotal-Pass Area, Kohat Range, N. Pakistan - Khan, Mohammad Asif; Turi, Karamat Ali; Abbasi, Iftikhar Ahmed (Journal of Himalayan Earth Sciences, 1990)
The Main Boundary Thrust is a wide, complexly folded and faulted zone which uplifted the Kohat range, and tectonically emplaced the Mesozoic-Cenozoic shelf carbonate succession over the Tertiary molasse sediments. The MBT zone is characterized main by major thrust faults both imbricate and duplex type and tight folds. Tight folding along the MBT zone resulted in the formation of out-of-the syncline faulting. Late stage (post folding and thrust faulting) development of normal faults at the base of the Paleocene succession further deformed the MBT zone in the Kohat area. The Paleocene strata in the hanging wall of southward propagating normal faults is subhorizontal to shallowly dipping northward, and lies discordantly over the Mesozoic succession. The normal faults are of localized nature in the MBT zone and are reported for the first time from the Kohat range. The normal faults may have exploited the weaker horizons generated during earlier thrusting such as out-of-the syncline fault s. Presence of thick fault breccia along the fault plane suggests that these structures may have formed close to near Surface conditions during uplift of the Kohat range